Alveolar rhabdomyosarcoma: origin and prognostic implications of molecular findings - Pilar Eguía-Aguilar; Briceida López-Martínez; Carmen Retana-Contreras; Mario Perezpeña-Diazconti (Permanyer, 2016)
We present the case of a 2-year-old male patient with a facial tumor partially treated with chemotherapy before his admission to our institution. The tumor involved from the frontal region to the maxillary floor, the orbit, and the maxillary and sphenoid sinuses. The histopathological diagnosis revealed a stage IV alveolar rhabdomyosarcoma with infiltration to bone marrow and cerebrospinal fluid. He was managed with four cycles of adriamycin, actinomycin, cyclophosphamide and vincristine; cisplatin and irinotecan were added to the last cycle. The tumor had a 50% size reduction, but the patient died after a neutropenia and fever episode. The aggressive behavior of alveolar rhabdomyosarcoma has been associated with the expression of oncogenic fusion proteins resulting from chromosomal translocations, particularly t(2;13) (q35;q14) PAX3/FOXO1, and t(1;13) (p36;q14) PAX7/FOXO1 which were present in this patient.